The shape of luck and competition in winner-take-all tournaments - Dmitry Ryvkin; Mikhail Drugov (Theoretical Economics, 2020)
In winner-take-all tournaments, agents' performance is determined jointly by effort and luck, and the top performer is rewarded. We study the impact of the ''shape of luck'' – the details of the distribution of performance shocks – on incentives in such settings. We are concerned with the effects of increasing the number of competitors, which can be deterministic or stochastic, on individual and aggregate effort. We show that these effects are determined by the shape of the density and failure (hazard) rate of the distribution of shocks. When shocks have heavy tails, aggregate effort can decrease in the number of competitors.
Keywords: C72; D72; D82; 330; Tournament; competition; heavy tails; stochastic number of players; unimodality; log supermodularity; failure rate